ANALISIS COST OF ILLNESS PADA PASIEN DIABETES MELLITUS DENGAN TERAPI GLIMEPIRIDE-METFORMIN RAWAT JALAN PESERTA BPJS DI PUSKESMAS KETAPANG II KOTA SAMPIT - Apriliana, Nur Ghina; Pristianty, Liza; Hidayati, Ika Ratna (Brawijaya University, 2023)
Background : Diabetes mellitus is a chronic disease that affects the costs incurred by patients during illness. The financing issued for the treatment of diabetes mellitus diseases can be measured using Cost of Illness analysis.Research Objectives : To find out the total cost of treatment of diabetes mellitus patients BPJS participants with Glymepiride-Metformin therapy for one year.Method : This study used a non-probability sampling technique with an accidental sampling method. This research conducted at Ketapang II Health Center with sample total 45 people. The instrument used a structured interview which was previously tested for validity. Data were analyzed using Microsoft Excel.Result and Conclusion : The estimate total cost of treatment of diabetes mellitus with outpatient glimepiride-metformin therapy of Indonesia Health Insurance participants at Ketapang II Health Center in Sampit city for one year is Rp.623.760 - Rp.4.475.520. The direct medical cost per patient is Rp.143.760 - Rp.2.787.120. Non-medical direct cost is Rp.0 - Rp.188.400. Indirect cost is Rp.480.000 - Rp.1.500.000. High cost are more expensive but the frequency of visits and patient compliance are orderly so that the therapeutic effect achieved is good, while the low cost is cheaper but the frequency of patient visits and patient compliance are not orderly so that the therapeutic effect achieved is less good and not maximal.